İNTERNET BAĞIMLILIĞI VE MEDYA KULLANIMI: ÜNİVERSİTE ÖĞRENCİLERİ ÜZERİNE BİR ARAŞTIRMA. - KALAMAN, Sefer; BAT, Mikail (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2016)
This study aims to determine the internet addiction levels of university students and indicate their usages of traditional media and internet. Face to face survey method was used in the study. This survey was prepared and done after the analyses of the subjects such as internet, internet addiction, traditional media and new media, and literature review related to them. Data of the survey done by 366 undergraduate students of Bozok University in 2016 were analyzed by SPSS program. According to these results, the internet addiction levels of students were high. Besides, they use new media more than traditional media. In this analysis, their genders, ages and income levels were also compared with different variables, and significant results were found.